Prevalence of Beta Thalassemia Trait in Semi-Urban Population of Karachi (Medical Forum Monthly, 2022)
Objective: To evaluate the prevalence of Beta Thalassemia Trait in Semi-urban Population of Karachi.Study Design: Comparative Cross-sectional studyPlace and Duration of Study: This study was conducted at the Department of Medicine, Baqai Medical University, Karachi and its affiliated teaching hospitals in Karachi, from July 2021 to September 2021.Materials and Methods: A total of 578 individuals were included in study, who were admitted in the medical ward and visiting out patients department (OPD) of the teaching hospital (Medical and obstetrics departments) of the Baqai medical university, Karachi. Patients with evidence of active blood loss, an acute or chronic inflammatory disorder, malignancy, recent surgery or pregnancy were excluded from the study. Complete blood count (CBC) was performed in all include individuals by using sysmex hematology analyzer. Mentzler’s index was calculated and applied to identify the beta thalassemia carriers. Difference between RBC parameters of normal and carrier population was also compared.Results: The 42 (7.2%) individuals among study population were suspected to have beta thalassemia trait on basis of Mentzler’s index. In normal population Mentzler’s index was 19.92±4.55 and in beta thalassemia trait (carrier) Mentzler’s index was 10.15±3.33. It reliably detected microcytosis (positive predictive value of 95.2%). Statistically significant difference (p<0.05) of RBC parameters was noted between normal and suspected carrier groups.Conclusion: RBCs parameters can reliably be used to screen and target thalassemia carriers.